2021
DOI: 10.1177/07334648211028391
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health Literacy and Socioeconomic Status with Oral Health Among Older Adults in Ghana: A Moderation Analysis of Social Capital

Abstract: We examined the moderating role of social capital (SC) in the association of socioeconomic status (SES) and health literacy (HL) with oral health (OH) status and the intentions to use OH services (IUOHS) among older Ghanaians. Data were derived from a cross-sectional survey ( n = 522) and analyzed using ordinal and binary logistic regressions. Bridging SC moderated the relationship between HL and oral health status ( B = 0. 0.117, p < .05) and the association of SES with IUOHS (adjusted odds ratio [AOR] = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…This study analysed the responses of 1929 participants. Detailed descriptions of the broader study’s sampling process have been reported elsewhere [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study analysed the responses of 1929 participants. Detailed descriptions of the broader study’s sampling process have been reported elsewhere [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…A confidence level of 95%, sample error of 0.05, and an assumption that 50% of respondents would provide consistent responses ( 52 ). Detailed information about the study design and sampling had been reported elsewhere ( 53 , 54 ).…”
Section: Methodsmentioning
confidence: 99%
“…As in the case of other measures of health, socioeconomic determinants are a substantial source to explain the diversity of oral health conditions among older persons (Amoah et al, 2021; Schensul et al, 2020). What we do know is that people facing adverse social environments have worse oral health on average than those with high socioeconomic status (Gülcan et al, 2015; Tsakos, 2011).…”
Section: Introductionmentioning
confidence: 99%